Impact of active coping, religion and acceptance on quality of life of patients with breast cancer in the department of radiotherapy, UCH, Ibadan (2014)
Background- A breast cancer diagnosis as well as the treatment that follows has considerable consequences on women’s physical functioning, psychological health and overall well-being, resulting in significant interference with patients’ quality of life (QoL). Purpose The study seeks to assess the impact of active coping, religion and acceptance on the QoL of patients with breast cancer. Participants- This study, which is descriptive in nature, assessed the QoL and coping mechanism of 110 patients with breast cancer receiving treatment at the radiotherapy clinic in the University College Hospital (UCH). The patients had an age range of 25–75, an average age of 46.82 and an SD of 10.55. Male patients were 4 (3.60%), while 106 (96.40%) were female. Currently married participants were 84 (76.40%), while 26 (23.60%) were not. Methods- Data was collected using the Functional Assessment of Cancer Therapy-Breast (FACT-B) V.4 QoL questionnaire and Carver’s Brief Cope questionnaire. Results- Analysis of data showed that significant differences were found between participants who used active coping, religious coping and acceptance more than those who did not in the overall QoL (p<0.05) as well as in some of the QoL dimensions. Conclusions- Significant differences exist in the QoL of patients with breast cancer based on the coping style they adopt. Patients with breast cancer should be helped to adopt coping styles that would enhance their QoL.